UiTM Vehicle Booking System (UVEBS) / Zura Rohayu Mat Bidin - Mat Bidin, Zura Rohayu (2014)
Web-based applications are programs that run on Web servers and use Web pages as user interface. The application usage of Internet website and online booking systems are currently dominating the modem information technology which gives many advantages to people. For that reasons, the web based system project entitled “UiTM Vehicle Booking System (UVEBS)” is developed to ease applicant in making vehicle booking process and administrator to manage vehicle booking for “Unit Kenderaan” of UiTM (Terengganu). Before this system has been develop, staffs and students need to fullfil the booking form manually and it creates many problems for the users that want to book the vehicle and the administrators to handle the information about the booking. Therefore, the file is not in good condition and probability of the file being lost is very high. UVEBS enables the applicants to register their account, update their profile and make vehicle booking. Besides that, the administration can add staffs, vehicles, approve the vehicle booking as well as updating and deleting the records information. The evaluation technique that had been used in completing the project were distributed questionnaires to students and staffs in UiTM (Terengganu). Overall from the results, the evaluation indicated that contents construct shows the highest mean and standaid deviation (Mean = 3.99, SD = 0.67725) . It means that most of the respondents agree about the contents which had provided in the system. Therefore, the interface design and functionality of the UVEBS web based system can be improved in future by other researcher.